KAJIAN HUKUM TERHADAP TINDAK PIDANA KORUPSI DALAM PERBANKAN (STUDI PUTUSAN NOMOR : 79/Pid.Sus.K/2012/PN.MDN.) - Ahmad Fadly; Liza Erwina; Mahmud Mulyadi (Jurnal Mahupiki, 2015)
ABSTRAK KAJIAN HUKUM TERHADAP TINDAK PIDANA KORUPSI DALAM PERBANKAN (STUDI PUTUSAN NOMOR : 79/Pid.Sus.K/2012/PN.MDN.) AHMAD FADLY[1] LIZA ERWINA,SH.,M.Hum[2] Dr.MAHMUD MULYADI,SH.,M,Hum[3] Study of law toward corruption in banking world is a normatif study when bank staff abuses authority in a banking company could be had done corruption. In case of prudential banking in which regulated law no. 10 year 1998 about banking stating how the regulations rule the bank staff commiting to corruption by violating or disobeying the stages of rule conduct. The regulation about corruption in terms of banking requires understandings about 2 special laws which law no. 31 year 1999 Jo. Law no. 20 year 2001 and law no. 7 year 1992 jo. Law no. 10 year 1998. Corruption and banking commited crime also requires a common ground in which needed to decide whether and corruption crime or banking crime. Relating to the abuse of profession conducted by a bank staff includes corruption crime or banking crime also the appliance of lex specialis sistematic derogate lex generalis principles in which a case regulated by two laws. In order to comprehend a banking related corruption, we need to understand the case standing in verdict no. 79/Pid.Sus.K/2012/PN.MDN. therefore we could analyse it legally. Accoring to normative research there is no corruption commited violance conducted by the staff of BNI SKM Medan which caused a loss during the periode of time. According to the descriptions above, the objective of corrption related study of law in banking is to build law priciples on when an individual is corruption allleged and to comprehend conducts of law comprised in a verdict. [1] Mahasiswa Fakultas Hukum Universitas Sumatera Utara [2] Dosen Pembimbing I, Dosen Fakultas Hukum Universitas Sumatera Utara [3] Dosen Pembimbing II, Dosen Fakultas Hukum Universitas Sumatera Utara